PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN ROKOK DI BURSA EFEK INDONESIA PERIODE 2014-2021 - Soesilawati Soema Atmadja (PUTRA JAWA PUBLISHER, 2023)
This study aims to empirically examine the effect of partial and simultaneous financial ratios (Current Ratio, Net Profit Margin, Debt to Asset Ratio, Total Assets Turn Over) on Profit Growth in Cigarette Companies listed on the Indonesia Stock Exchange for the 2014-2021 period. The population in this study comprises cigarette companies listed on the Indonesia Stock Exchange, and the sampling technique used is purposive sampling, with a final sample size of 4 companies. The analysis technique in this study employs multiple linear regression analysis with IBM SPSS Statistics 26 software. From the results of the study, it is partially shown that the Current Ratio variable has no effect on Profit Growth. For the Net Profit Margin variable, Debt to Asset Ratio variable, and Total Assets Turn Over variable, there is a partial and significant effect on Profit Growth. Simultaneously, the variables show a significant effect on Profit Growth. The results of the calculation of the Coefficient of Determination indicate a value of 0.765 or 77%.